(untitled) (Global Journal of Science Frontier Research, 2018)
In the article are obtained the conversions pour on upon transfer of one inertial reference system (IRS) to another. In contrast to the conversions of Lorenz the basis of such conversions are the conversions of Galileo and the symmetrical laws of induction. In this case the total derivatives, which consider their convective part, are used. This made possible to explain the phenomenon of phase aberration of light and to explain the reasons of the transverse Doppler effect, who is only apparent effect.